A phenotype-directed chemical screen identifies ponalrestat as an inhibitor of the plant flavin monooxygenase YUCCA in auxin biosynthesis - Zhu, Ying (J Biol Chem, 2019)
Plant development is regulated by both synergistic and antagonistic interactions of different phytohormones, including a complex crosstalk between ethylene and auxin. For instance, auxin and ethylene synergistically control primary root elongation and root hair formation. However, a lack of chemical agents that specifically modulate ethylene or auxin production has precluded precise delineation of the contribution of each hormone to root development. Here, we performed a chemical genetic screen based on the recovery of root growth in ethylene-related Arabidopsis mutants with constitutive “short root” phenotypes (eto1–2 and ctr1–1). We found that ponalrestat exposure recovers root elongation in these mutants in an ethylene signal–independent manner. Genetic and pharmacological investigations revealed that ponalrestat inhibits the enzymatic activity of the flavin-containing monooxygenase YUCCA, which catalyzes the rate-limiting step of the indole-3-pyruvic acid branch of the auxin biosynthesis pathway. In summary, our findings have identified a YUCCA inhibitor that may be useful as a chemical tool to dissect the distinct steps in auxin biosynthesis and in the regulation of root development.